Methods of Using Music and the Bass Guitar in Teaching - Husar, Maj (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores various ways in which music and the bass guitar can be utilized in teaching. Research highlights numerous possibilities and potential factors that can be applied in music lessons as well as in other primary-level subjects. These elements are presented and explained through the discussion of research findings, accompanied by concrete examples. The chapter examines and defines the use and role of the bass guitar in teaching and how it can be effectively integrated into the curriculum. The bass guitar offers many opportunities for its application, and the connections supported by research are emphasized. Music and the bass guitar serve as versatile tools for teachers, significantly influencing the process and effectiveness of lessons when employed effectively.